Insights into preferences for irrigation pumps in West Bengal: An application of best-worst-scaling - Lountain, Sophie; Burton, Michael; Cooper, Bethany; Crase, Lin; Rigby, Daniel (Australian Journal of Agricultural and Resource Economics, 2024)
This paper presents an analysis of the heterogeneous preferences of farmers towards groundwater pump technologies. The research uses primary field data drawn from West Bengal, India, where the progressive feminisation of agriculture has been well-documented. We employ a paired comparison technique to explore how gender impacts the preferences towards different attributes of pumping technology. Our findings illustrate that preferences for irrigation pump attributes vary significantly between farmer groups, and policies that put technologies in the hands of some groups versus others could have significantly different impacts on how pumps are ultimately used.
Keywords: India; Irrigation Technology; Paired Comparison; West Bengal; Agricultural Development